Face recognition system with vigenere cipher cryptography for document security - Sukri Sukri; Luluk Elvitaria; Wandiah Ayu Barus (Institute of Computer Science (IOCS), 2023)
The issue of data security and confidentiality is one of the most important aspects of an information delivery system. In this case, it is closely related to how important it is that the information be sent and received by interested parties. Information will no longer be useful if, in the middle of the delivery process, the information is intercepted or hijacked by unauthorized people. Computer security is something that is very important in this information age, especially for an organization or company. Data confidentiality The computer security problem is very important in this information age, especially for an organization or company because documents are some of the most important data for the continuity of the company's operations. The branch of science that studies ways to secure data is known as